Manganese Induces IGF-1 and Cyclooxygenase-2 Gene Expressions in the Basal Hypothalamus during Prepubertal Female Development - Hiney, Jill K. (Oxford University Press, 2011)
Precocious puberty is a significant child health problem, especially in girls, because 95% of cases are idiopathic. Our earlier studies demonstrated that low-dose levels of manganese (Mn) caused precocious puberty via stimulating the secretion of luteinizing hormone–releasing hormone (LHRH). Because glial-neuronal communications are important for the activation of LHRH secretion at puberty, we investigated the effects of prepubertal Mn exposure on specific glial-derived puberty-related genes known to affect neuronal LHRH release. Animals were supplemented with MnCl(2) (10 mg/kg) or saline by gastric gavage from day 12 until day 22 or day 29, then decapitated, and brains removed. The site of LHRH release is the medial basal hypothalamus (MBH), and tissues from this area were analyzed by real-time PCR for transforming growth factor α (TGFα), insulin-like growth factor-1 (IGF-1), and cyclooxygenase-2 (COX-2) messenger RNA levels. Protein levels for IGF-1 receptor (IGF-1R) were measured by Western blot analysis. LHRH gene expression was measured in the preoptic area/anteroventral periventricular (POA/AVPV) region. In the MBH, at 22 days, IGF-1 gene expression was increased (p < 0.05) with a concomitant increase (p < 0.05) in IGF-1R protein expression. Mn also increased (p < 0.01) COX-2 gene expression. At 29 days, the upregulation of IGF-1 (p < 0.05) and COX-2 (p < 0.05) continued in the MBH. At this time, we observed increased (p < 0.05) LHRH gene expression in the POA/AVPV. Additionally, Mn stimulated prostaglandin E(2) and LHRH release from 29-day-old median eminences incubated in vitro. These results demonstrate that Mn, through the upregulation of IGF-1 and COX-2, may promote maturational events and glial-neuronal communications facilitating the increased neurosecretory activity, including that of LHRH, resulting in precocious pubertal development.